The relationship between integrative motivation and Malay language achievement among chinese privateschool students. - Mahyuddin, Rahil; Teoh, Hee Chong; Elias, Habibah; Uli, Jegak (Common Ground Publishing, 2008)
The study investigates the relationship of Malay Language achievement to four attitude/motivation variables from Gardner’s socio-educational model: attitudes toward learning situation, motivation, integrative orientation, and instrumental orientation. The socio-educational model of second language acquisition postulates that language learning is a dynamic process in which affective variables influence language achievement. The sample consisted of 318 Grade 10 students in formal classroom settings in Chinese private schools in Kuala Lumpur. The results clearly demonstrated the correlations between language achievement and motivation (Cramers’ V= 0.195) are higher than those between achievement and integrative motivation, attitude towards learning situation, integrative orientation, or instrumental orientation. However, the overall results indicate that the correlations between achievement and those variables are weak. Only integrative motivation and motivation show a significant correlation with the Malay Language. In conclusion, the findings basically confirmed Gardner’s socio-educational model.